Abstracts (Edited by Prof. Tahir Mahmood) - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2008)
Central Corneal Thickness Measurements Using Orbscan II, Visante, Ultrasound, and Pentacam Pachymetry After Laser in Situ Keratomileusis for Myopia Thomas Ho, Cheng ACK, Rao SK, Lau S, Leung CKS, LamDSC J Cataract Refract Surg 2007; 33: 1177-82 Phacotrabeculectomy: Assessment of outcomes and surgical improvements George J.C. Jin, MD, PhD, Alan S. Crandall, MD, Jason J. Jones, MD J Cataract Refract Surg 2007; 33: 1201-1208 Prospective Visual Evaluation of Apodized Diffractive Intraocular Lenses Alfonso JF, Fernandez-Vega L, Baamonde MB, Montes-Mico R J Cataract Refract Surg 2007; 33: 1235-43 Visual Acuity and Contrast Sensitivity: Acrysof Restor Apodized Diffractive Versus Acrysof SA60AT Monofocal Intraocular Lenses Vingolo EM, Grenga PL, Lacobelli L, Grenga G J Cataract Refract Surg 2007; 33: 1244-7 Intraocular Lens Centration and Visual Outcomes After bag-in-the-Lens Implantation VerbruggenKHM, Rozema JJ, Gobin L, Coeckelbergh T, Groot VD, Tassignon MJ, J Cataract Refract Surg 2007; 33: 1267-2.